2005
DOI: 10.1111/j.1365-313x.2005.02439.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation tagging of a gene for a protein with novel class of CCT‐domain activates expression of a subset of sugar‐inducible genes in Arabidopsis thaliana

Abstract: SummaryIn the current studies, we examined sugar-inducible gene expression using the Arabidopsis thaliana line sGsL, which carries luciferase (LUC) and b-glucuronidase (GUS) reporter genes under the control of a 210-bp promoter derived from the sweet potato sporamin gene (Spo min ). We isolated an enhancer activation-tagged mutant of this line that showed high-level expression of LUC and GUS under non-inducing low-sugar conditions. The Activator of Spo min ::LUC2 (ASML2) gene located close to the enhancer enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
(59 reference statements)
0
31
0
Order By: Relevance
“…A WRKY transcription factor in sweet potato, SPF1, is able to bind to the sugarresponsive sporamin and β-amylase promoters (Ishiguro and Nakamura, 1994), and this suggests that SPF1 acts as a repressor (Rook et al, 2006). In A. thaliana, Masaki et al (2005) reported an activator of Spo min -LUC2 (ASML2; locus number At3g12890), which is a protein belonging to CCT (Constans, Constans-like, TOC1) domain proteins, functions as a transcriptional activator of ApL3, and expression of ASML2 gene is enhanced by sugars in A. thaliana. However, DNA-binding transcriptional activators that regulate the expression of the AGPase genes in response to sugar have not been identifi ed.…”
mentioning
confidence: 99%
“…A WRKY transcription factor in sweet potato, SPF1, is able to bind to the sugarresponsive sporamin and β-amylase promoters (Ishiguro and Nakamura, 1994), and this suggests that SPF1 acts as a repressor (Rook et al, 2006). In A. thaliana, Masaki et al (2005) reported an activator of Spo min -LUC2 (ASML2; locus number At3g12890), which is a protein belonging to CCT (Constans, Constans-like, TOC1) domain proteins, functions as a transcriptional activator of ApL3, and expression of ASML2 gene is enhanced by sugars in A. thaliana. However, DNA-binding transcriptional activators that regulate the expression of the AGPase genes in response to sugar have not been identifi ed.…”
mentioning
confidence: 99%
“…Although a large rearrangement of chromosome 3 occurred at the site of T-DNA integration in this mutant, expression of a gene designated as ASML2 located immediately downstream of the enhancer was significantly higher in the mutant compared to the sGsL plants. Similar to the original mutant, sGsL plants that express ASML2 cDNA under the CaMV 35S promoter showed enhanced expression of not only LUC and GUS reporters but also endogenous Atb-Amy, ApL3, and VSP2 genes compared to the sGsL plants ( Figure 3B; Masaki et al 2005b). Unlike the original mutant, the 35S::ASML2 transformants did not show severe defects in growth and development.…”
Section: Asml2 With Novel Class Of Cct-domain Activates Expression Ofmentioning
confidence: 76%
“…Rather, it enhanced the level of expression of Spo min in response to sugars (Figure 3c; Masaki et al 2005b). Similar to Spo min , expression of Atb-Amy, ApL3 and VSP that are enhanced in the 35S::ASML2 transformants are inducible by various metabolizable sugars.…”
Section: Asml2 With Novel Class Of Cct-domain Activates Expression Ofmentioning
confidence: 99%
“…In addition, the GATA-type zincfinger protein expressed in inflorescence meristem, ZIM, and two homologous proteins, ZML1 and ZML2, contain a CCT domain (Shikata et al 2004). ASML2 family proteins also contain a CCT domain, without any of the domains that COL, APRR and ZIM family proteins have (Masaki et al 2005). The TCR1 gene (AGI code; At1g07050) is predicted to contain two introns ( Figure 1B) and encode a putative protein of 195 amino acids with high homology to a CCT domain at its C-terminus ( Figure 1C).…”
Section: Gene Notementioning
confidence: 99%
“…The CCT domain-containing proteins are found in a wide range of flowering plants, but have not been described in mammals or yeast. The CCT domain-containing proteins have been considered to function as transcriptional regulators, implicated in diverse processes such as photoperiodic flowering (Putterill et al 1995), regulation of circadian rhythms (Strayer et al 2000), light signaling (Kaczorowski and Quail 2003) and gene expression in response to sugars (Masaki et al 2005). In Arabidopsis, a CCT domain has been identified in CO and 16 COL proteins (Putterill et al 1995;Robson et al 2001), TOC1 and four other structurally related pseudo-response regulators, APRRs (Matsushika et al 2000;Strayer et al 2000) ( Figure 1A).…”
mentioning
confidence: 99%